Tumor microbiome analysis provides prognostic value for patients with stage III colorectal cancer - Kim, Jae Hyun; Yu, Jongwook; Kim, Dong Keon; Lee, Seunghun; Lee, Seung Hyun; Ahn, Byung Kwon; Kim, Tae Il; Park, Seun Ja (Frontiers in Oncology, 2023)
Introduction Although patients with colorectal cancer (CRC) can receive optimal treatment, the risk of recurrence remains. This study aimed to evaluate whether the tumor microbiome can be a predictor of recurrence in patients with stage III CRC. Methods Using 16S rRNA gene sequencing, we analyzed the microbiomes of tumor and adjacent tissues acquired during surgery in 65 patients with stage III CRC and evaluated the correlation of the tissue microbiome with CRC recurrence. Additionally, the tumor tissue microbiome data of 71 patients with stage III CRC from another center were used as a validation set. Results The microbial diversity and abundance significantly differed between tumor and adjacent tissues. In particular, Streptococcus and Gemella were more abundant in tumor tissue samples than in adjacent tissue samples. The microbial diversity and abundance in tumor and adjacent tissues did not differ according to the presence of recurrence, except for one genus in the validation set. Logistic regression analysis revealed that a recurrence prediction model including tumor tissue microbiome data had a better prediction performance than clinical factors (area under the curve [AUC] 0.846 vs. 0.679, p = 0.009), regardless of sex (male patients: AUC 0.943 vs. 0.818, p = 0.043; female patients: AUC 0.885 vs. 0.590, p = 0.017). When this prediction model was applied to the validation set, it had a higher AUC value than clinical factors in female patients. Conclusion Our results suggest that the tumor microbiome of patients with CRC be a potential predictor of postoperative disease recurrence.